Immunological features and prospectives in the treatment of chlamydial infection in women - Лахно, И. В. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
The article analyzes the pathogenetic peculiarities of chlamydial infection influence the reproductive female system. It was performed the emphasis on intracellular lesions initiated by the advent of the «master» followed by the death of epithelial cells of the fallopian tubes and replacement of connective tissue. It was shown the possibility of using tilorone as an antifibrotic agent to prevent formation of scarring of the fallopian tubes and peritubal adhesions.